A Thermo-Hygro-Coupled Model for Chloride Penetration in Concrete Structures. (22nd July 2015) - Damrongwiriyanupap, Nattapong; Limkatanyu, Suchart; Xi, Yunping
Abstract : Corrosion damage due to chloride attack is one of the most concerning issues for long term durability of reinforced concrete structures. By developing the reliable mathematical model of chloride penetration into concrete structures, it can help structural engineers and management agencies with predicting the service life of reinforced concrete structures in order to effectively schedule the maintenance, repair, and rehabilitation program. This paper presents a theoretical and computational model for chloride diffusion in concrete structures. The governing equations are taking into account the coupled transport process of chloride ions, moisture, and temperature. This represents the actual condition of concrete structures which are always found in nonsaturated and nonisothermal conditions. The fully coupled effects among chloride, moisture, and heat diffusion are considered and included in the model. The coupling parameters evaluated based on the available material models and test data are proposed and explicitly incorporated in the governing equations. The numerical analysis of coupled transport equations is performed using the finite element method. The model is validated by comparing the numerical results against the available experimental data and a good agreement is observed.